Combined Effects of Synaptic and Axonal Integrity on Longitudinal Gray Matter Atrophy in Cognitively Unimpaired Adults. (15th November 2022) - Saloner, Rowan; Fonseca, Corrina; Paolillo, Emily W.; Asken, Breton M.; Djukic, Nina A.; Lee, Shannon; Nilsson, Johanna; Brinkmalm, Ann; Blennow, Kaj; Zetterberg, Henrik; Kramer, Joel H.; Casaletto, Kaitlin B.
Abstract : Background and Objectives: Synaptic dysfunction and degeneration is a predominant feature of brain aging, and synaptic preservation buffers against Alzheimer disease (AD) protein-related brain atrophy. We tested whether CSF synaptic protein concentrations similarly moderate the effects of axonal injury, indexed by CSF neurofilament light [NfL]), on brain atrophy in clinically normal adults. Methods: Clinically normal older adults enrolled in the observational Hillblom Aging Network study at the UCSF Memory and Aging Center completed baseline lumbar puncture and longitudinal brain MRI (mean scan [follow-up] = 2.6 [3.7 years]). CSF was assayed for synaptic proteins (synaptotagmin-1, synaptosomal-associated protein 25 [SNAP-25], neurogranin, growth-associated protein 43 [GAP-43]), axonal injury (NfL), and core AD biomarkers (ptau181 /Aβ42 ratio; reflecting AD proteinopathy). Ten bilateral temporoparietal gray matter region of interest (ROIs) shown to be sensitive to clinical AD were summed to generate a composite temporoparietal ROI. Linear mixed-effects models tested statistical moderation of baseline synaptic proteins on baseline NfL-related temporoparietal trajectories, controlling for ptau181 /Aβ42 ratios. Results: Forty-six clinically normal older adults (mean age = 70 years; 43% female) were included. Synaptic proteins exhibited small to medium correlations with NfL ( r range: 0.10–0.36). Higher baseline NfL, but not ptau181 /Aβ42 ratios, predicted steeper temporoparietal atrophy (NfL × time: β = −0.08, p < 0.001; ptau181 /Aβ42 × time: β = −0.02, p = 0.31). SNAP-25, neurogranin, and GAP-43 significantly moderated NfL-related atrophy trajectories (−0.07 ≤ β's ≥ −0.06, p' s < 0.05) such that NfL was associated with temporoparietal atrophy at high (more abnormal) but not low (more normal) synaptic protein concentrations. At high NfL concentrations, atrophy trajectories were 1.5–4.5 times weaker when synaptic protein concentrations were low (β range: −0.21 to −0.07) than high (β range: −0.33 to −0.30). Discussion: The association between baseline CSF NfL and longitudinal temporoparietal atrophy is accelerated by synaptic dysfunction and buffered by synaptic integrity. Beyond AD proteins, concurrent examination of in vivo axonal and synaptic biomarkers may improve detection of neural alterations that precede overt structural changes in AD-sensitive brain regions.